2009
DOI: 10.1063/1.3233940
|View full text |Cite
|
Sign up to set email alerts
|

AC thermal imaging of a microwire with a fluorescent nanocrystal: Influence of the near field on the thermal contrast

Abstract: Intense 1.54 m fluorescence of Er 3 + / Yb 3 + codoped phosphate glass and the three-photon phenomenon of near infrared upconversion luminescence Physical characteristics and infrared fluorescence properties of sol-gel derived Er 3+ -Yb 3+ codoped TiO 2We have studied the temperature dependence of the visible fluorescence lines of 250 nm large PbF 2 nanocrystals codoped with Er 3+ and Yb 3+ ions. By gluing such a particle at the end of a sharp atomic force microscope tip, we have developed a scanning thermal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 30 publications
0
51
1
Order By: Relevance
“…-doped NPs; [36][37][38][39][40][41] Nanoscale IR thermometers from metal NPs based on blackbody radiation; 42 Scanning thermal microscopes based on Ln 3+ -doped NPs; 12,[43][44][45] Nanoscale thermocouples fabricated from point contact junctions; 23,46,47 Liquid-and solid-in-tube nanothermometers fabricated from nanotubes and based on temperature-dependent thermal expansion of liquids (e.g. gallium inside CNTs 48,49 or Pb-filled ZnO nanotubes 50 ); Coulomb blockade nanothermometers from nanosized superconductor-insulator-metal tunnel junctions based on the Coulomb blockade of tunneling; 51,52 Complex structured nanothermometers from MEMS based on temperature-dependent resonator quality factor 53 or Fermilevel shift.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…-doped NPs; [36][37][38][39][40][41] Nanoscale IR thermometers from metal NPs based on blackbody radiation; 42 Scanning thermal microscopes based on Ln 3+ -doped NPs; 12,[43][44][45] Nanoscale thermocouples fabricated from point contact junctions; 23,46,47 Liquid-and solid-in-tube nanothermometers fabricated from nanotubes and based on temperature-dependent thermal expansion of liquids (e.g. gallium inside CNTs 48,49 or Pb-filled ZnO nanotubes 50 ); Coulomb blockade nanothermometers from nanosized superconductor-insulator-metal tunnel junctions based on the Coulomb blockade of tunneling; 51,52 Complex structured nanothermometers from MEMS based on temperature-dependent resonator quality factor 53 or Fermilevel shift.…”
Section: +mentioning
confidence: 99%
“…200 A number of developments based on new cantilevers and new AFM-based temperature measuring techniques have been stated in recent years. 43,45,[201][202][203][204][205][206][207][208][209][210] Sadat et al 23 have reported a thermometric AFM-based technique which does not require integrated temperature sensors in AFM probes. The technique allows direct mapping of topography and temperature fields of metal surfaces with $0.01 degree temperature resolution and <100 nm spatial resolution.…”
Section: Scanning Thermal Microscopymentioning
confidence: 99%
“…Among phosphors, such as organic dyes, [ 3 ] polymers, [ 4 ] semiconductor nanocrystals, [ 5 ] lanthanide (Ln)-based materials are the most versatile thermal probes used in luminescent nanothermometers. [ 6 ] Several examples of such materials demonstrating their application in sensing or mapping at the submicrometer scale were reported: Er 3+ / Yb 3+ co-doped fl uoride glass [ 7 ] or PbF 2 nanoparticles, [ 8 ] glued at the extremity of an atomic force microscope scanning tip, NaYF 4 :(Er 3+ ,Yb 3+ ) [ 9 ] and Ln-doped NaGdF 4 core-shell nanoparticles; [ 10 ] Y 2 O 3 :Eu 3+ , [ 11 ] Y 3 Al 5 O 12 :Ce 3+ , [ 12 ] and Mo sensitized rareearth oxide nanoparticles; [ 13 ] and siloxane-based nanoparticles incorporating a Eu 3+ tris(β-diketonate) complex. [ 14 ] The temperature determination is usually based on the change of the luminescence intensity or decay times.…”
mentioning
confidence: 99%
“…1,2 On the other hand, the peculiar emission features typical of lanthanide (Ln 3+ ) ions, such as long lifetimes, large Stokes/anti-Stokes shifts, narrow bandwidth emissions, high luminescence quantum yields and ligand-dependent sensitization, have been used in non-invasive thermometry. [5][6][7][8][9][10][11][12][13] In the last decade, a step-forward in the field was the introduction of reliable and robust selfreference thermometers based on the intensity ratio of two f-f transitions (e.g., 5 D 0 → 7 F 2 , Eu 3+ , and 5 D 4 → 7 F 5 , Tb 3+ ) using nanoparticles, 14,15 nanobeads incorporating magnetic heathers and thermometers, 16 organic-inorganic hybrid films, 17 and metal-organic frameworks (MOFs). [18][19][20][21] The most attractive feature of such molecular thermal probes is its intrinsic possibility of engineering the operating temperature range and sensitivity using a judicious choice of lanthanide ions, host matrix and/or ligands.…”
mentioning
confidence: 99%